Improving eighth graders’ Lexical Competence by using Translation as a Teaching Technique (2018)
The birth of the Communicative Approach in 1956 and the tedious repetition that learners had to undergo with the Grammar-Translation method implied the stigmatization of the use of the first language in classroom environments. Nevertheless, nowadays, there are authors who support the first language use in foreign language lessons and propose new ways to include it in order to develop the four communicative skills. In this work, the researchers studied the impact of pedagogical translation with an 8 th grade class to develop their lexical competence in English. The perception of the students and the language interaction were established by means of data collection instruments such as interviews and observations. In addition, the strategy was adapted and integrated into a pedagogical intervention taking into account previous works like those of Leonardi (2011), Ballester & Chamorro (1991), and Koletnik (2012), and topics from the Suggested Curriculum for the English subject (2016). The results presented in the chapter of data analysis determined that Pedagogical Translation works as a tool to develop lexical knowledge causing a significant improvement, and the positive general perception shown by students displays the acceptance and the benefits of its implementation in foreign language teaching environments.